The effect of rifampicin administration on the pharmacokinetic profile of glipizid in normal subjects - Luciana Kuswibawati, Luciana Kuswibawati (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2002)
Background: The use of antituberculosis drugs among diabetic patients is not infrequent. Among these, glipizide is one of the widely used antidiabetic drugs. The use of this second generation sulfonylurea in combination with rifampicin is common.Rifampicin is known as enzyme inductor that can influence other drugs metabolism used in combination.Objective: To investigate the effect of rifampicin pretreatment on the pharmacokinetic parameters of glipizide among 12 Indonesian healthy volunteers.Methods: Using randomized crossover design, volunteers were divided into two groups, i.e control and rifampicin pretreatment groups. Before starting the experiment, the pretreatment group was given 450 mg of rifampicin orally which should be taken daily for 7 days. Subsequently, a single dose of 5 mg glipizide was ingested to control and the pretreatment group as well. After oral administration of single dose of 5 mg glipizide, the samples were collected serially at 0; 0.5; 0.75; 1; 1.5; 2; 2.5; 3; 4; 5; 7; 9 and 12 hours to analyze blood glipizide level. High Pert ormace Liquid Chromatography (HPLC) method was used to analyze glipizide pharmacokinetic profile. From the data obtained, the pharmacokinetic parameters were calculated using noncompartment model.Results: The results showed that there were no significant change in the value of Tmax, Cmax, Ka, significant increases clearence (CI) 101.8% and elimination rate constant (Kel) 116.7% of the rifampicin pretreatment group. The elimination half life (T1/2) were shortened 39.5% from 3.8 to 2.3 hours (p<0.01). AUCO-12 dan AUCO--- of the rifampicin pretreatment group decreased by 38.7% and 44.0% respec-tively (p<0.05).Conclusion: Pretreatment with rifampicin 450 mg once daily for 7 days did not change absorption pharmacokinetic parameters of glipizid single dose of 5 mg but accelerated the elimination pharmacokinetic parameters of glipizide. Keywords: rifampicin-glipizide-drug interaction-pharmacokinetic-DM